The role of the principal in leading and managing teaching and learning in Lesotho : a case study of distributed leadership in two primary schools in the distric of Botha-Bothe. - Sefeane, Litlhaka A. (My University, 2015)
Education in Lesotho was not available to all children until the year 2000 with the introduction of the Free Primary Education policy. Since then, the huge rise in enrolments, the abolition of school fees, the effects of new policies and the problems of HIV/AIDS have expanded the demands on the principal while limited human and financial resources threaten the quality of education. This study investigates the role of two principals in the Botha Bothe district in the leadership and management of teaching and learning as well as the strategies they employ to overcome the difficulties. Special attention is given to distributed leadership so that accountable, effective and efficient leadership and management can take place. Qualitative methodology has been used through instruments such as questionnaires, followup interviews and observations to obtain data from the principals at the schools, one deputy principal and three to four teachers each. The findings indicate that the perceived main role of the principal at both these schools is managing and leading teaching and learning to the required standard. In both schools, it has been found that principals share their complex managerial duties with teachers and deputy principals, that most teachers willingly give of their time to contribute to the success of the school in this way and understand the need for doing so. By incorporating and respecting teachers’ contributions to leadership, the study shows how both principals cope with their particular leadership challenges. While the strategies used can serve as a guide to others within similar contexts, the researcher suggests that the education authorities in Lesotho need to be more aware of the problems facing schools, should make sufficient human and physical resources available to help principals manage the schools properly, and provide for AIDS orphans adequately. In addition, support for quality education in the form of ongoing professional development for both principals and teachers is needed, and more research needs to be conducted related to education issues in Lesotho.
Keywords: Leading and managing; Distributed leadership; Instructional leadership; Teaching and learning; Role of the principal